An Organic Fertilizer via Mixtures of Chicken Manure as the Main Materials For Okra Plant Growth - ANUAR, AMIRUL ZARIF; MOHD ALIFF HAIQAL BIN MOHD ARIS, (Multidisciplinary Applied Research and Innovation, 2023)
Many modern farmers used chemical fertilizer as their main way to fertilize their crop and vegetation, but this type of fertilizer contain harmful substance Which can leads to environmental issues and human health problems. In this study, The main purpose of this study was to produce the organic fertilizer made up of chicken manure, eggshell powder and washed rice water. The substance are chicken manure that contain nitrogen(Na) and eggshell powder with phosphorus(P) and washed rice water waste provide the potassium(K). All this material are used to fine the best mixture and ratio. Chicken manures are proven to have all the beneficial nutrient needed for plant growth as other materials will help the effectiveness of the fertilizers. Six bottles are prepared with each of them are labelled A-F. Bottled A,B and C are prepared with different ingredient while bottle D,E and F are prepared with all the material added but different ratio with each bottle. From the observation, it is included that the best fertilizers for the plant are the from bottle F which have (4:2:1:10) the best ratio of all plus the material needed for plant to grow.